An Anthropological Analysis of Canadian Music Festivals: Tournaments of Value, Modes of Festival Consumption, Tension, Conflict, and Struggle in the Context of Vancouver Island Music Festival - Moranz, Gillian G, Ms. (Scholarship@Western, 2014)
During the summers of 2011/2012 I conducted research for my Undergraduate Thesis concerning folk, roots, and music festivals from British Columbia to Newfoundland. This study has focused on cultural elements of community, intention, performance, value, capital, and exchange, and was conducted within seventeen different festivals sites from western Canada to the Maritimes. The following paper represents one chapter of my final Thesis and showcases ethnographic and observational data collected at Vancouver Island Music Festival in Comox, British Columbia in July 2011.